Preparation and quality characteristics of gluten‐free potato cake. Issue 11 (23rd September 2020) - Li, Mei; Sun, Hong‐Nan; Mu, Tai‐Hua; Tian, Shi‐Long; Ji, Lei‐Lei; Zhang, Du‐Qin; Li, Shou‐Qiang; Ge, Xia; Cheng, Jian‐Xin; Tian, Jia‐Chun
Abstract: This study aimed to assess the quality characteristics of potato gluten‐free cake. Sensory quality was most affected by the proportion of egg, followed by water and corn oil. The optimum formulation was potato flour 26.3g/100g, eggs 60 g/100 g, water 10 g/100 g, corn oil 3.0 g/100 g, salt 0.3 g/100 g, baking powder 0.2 g/100 g, and cream of tartar 0.2 g/100 g, with the sensory evaluation score 92.12. Compared with wheat cake, potato cake had lower fat and energy content, but higher dietary fiber, trace elements, and amino acids. Potato cake exhibited better texture and more volatile compounds than wheat cake. Electronic nose and tongue results showed a significant difference in flavor and taste between potato and wheat cakes. In addition, the antioxidant activity of potato cake was higher than wheat cake. In conclusion, potato flour is an ideal substitute for wheat flour in the manufacture of gluten‐free cake and potentially, other baked products. Practical applications: Celiac disease is a lifelong intolerance to the gliadin and glutenin protein components of wheat and to similar proteins found in rye, barley, and oats. Potato is a globally acceptable nutritious food and, therefore, an ideal raw material for gluten‐free food. In this study, potato powder was used to make potato flour cake and compared it with wheat flour cake, using single factor and orthogonal tests to optimize the cake formulation. A comprehensive evaluation was made, of appearance, quality, texture, nutrition, flavor, and stability to oxidation, so as to develop practical gluten‐free potato cake products, to expand the choice of gluten‐free foods, for the benefit of celiac disease sufferers.